Political Marketing and Its Impact on Democracy - Imam Sofyan (Communication Sphere, 2015)
ABSTRACTIn a modern political competition that is open and transparent, contestants need amethod that can facilitate the distribution of political products, such as new ideas, issues, partyideology, programs and leadership characteristics to the public. In order to win the election, theyshould be able to apply new political communication strategies that are more oriented to voters,and understand how this can be applied by implementing marketing strategies to promote thecandidate and their political values. However, the use of political marketing has an influence onthe health of democracy. Some scholars believe that it brings about benefits to the democracysystem. In spite of these positif impacts the use of political marketing has drawbacks as well.Keywords: Political Marketing, Political Campaign, Democracy